2013
DOI: 10.5897/ajar11.1390
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of Saponaria officinalis extracts against avian pathogenic Escherichia coli (APEC)

Abstract: In current study using Saponaria officinalis (Related to Caryophyllaceae family) hydroalcoholic extracts for in vitro growth inhibition of an avian isolated fatal Escherichia coli (isolated from coli CRDcomplex carcasses) were reported. The disc diffusion method was used for evaluation of the antibacterial effects of Saponaria extracts in comparison to some routine antibiotics. Minimum inhibitory concentration (MIC) of Saponaria extracts against avian pathogenic E. coli, APEC, using tube dilution technique was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…For example, saponins from Yucca exhibit antimicrobial activity against Gram-positive cells but do not act on Gram negative bacteria. However, S. officinalis extracts showed antibacterial action against Gram negative, avian pathogenic Escherichia coli (APEC) strains [68,69]. In general, the antibacterial activity of saponins is often weak, whereas significant antifungal activity has been observed.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…For example, saponins from Yucca exhibit antimicrobial activity against Gram-positive cells but do not act on Gram negative bacteria. However, S. officinalis extracts showed antibacterial action against Gram negative, avian pathogenic Escherichia coli (APEC) strains [68,69]. In general, the antibacterial activity of saponins is often weak, whereas significant antifungal activity has been observed.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…For this reason, the aim of this study was to evaluate the effect of cork functionalized with M. oleifera seed extract (MoSe), which as far as we know has not yet been elucidated, since studies with this material have been mainly focused on its use as a biocatalytic functional matrix with silver nanoparticles that efficiently reduced the growth of E. coli [23]. However, to confirm the antimicrobial effect of MoSe, it is necessary to apply faster methods than conventional ones to demonstrate the membrane cell disturbance caused by the bioactive compounds present in the seed extract [24,25]. Studies have reported that among these could be phytochemical compounds with antimicrobial properties that can reduce high cellular concentrations of pathogenic bacteria such as E. coli, Salmonella sp.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Veda et al, ethyl acetate extract of S. officinalis delivered the inhibition zone diameters of 12.67 ± 0.33, 14, 12.3 ± 0.33, 16, and 13.67 ± 0.33 mm against L. monocytogenes, Staphylococcus aureus, Streptococcus pneumoniae, E. coli, and Pseudomonas aeruginosa, while the inhibition zone diameters of the methanolic extract of this plant against these bacteria were obtained as 13.33 ± 0.33, 14.23 ± 0.33, 16, 19.67 ± 0.33, and 17.67 ± 0.33 mm, respectively (30). In another study, Nabinejad, who investigated the antimicrobial activity of S. officinalis extract against E. coli, reported that the inhibition zone diameters in the dilutions of 10, 15, and 20 microliters were equal to 16, 18, and 19 mm, respectively (31).…”
Section: Discussionmentioning
confidence: 98%